Design, Construction And Operational Plans Of An Electric Paddle Wheel For A Laminated Bamboo Slats River Cruise Boat - Heri Supomo; Eko Budi Djatmiko; Setyo Nugroho; Wikaranosa Scotiandharu Supomo (Department of Naval Architecture - Diponegoro University, 2023)
River cruise tourism in Indonesia has a moderately high potential as there are so many rivers in Indonesia that offer beautiful natural and urban views. However, majority of river cruiser boats still use outboard engines, both two-stroke and four-stroke combustion engines. The working system of the outboard engine is to carry out the combustion process of the fuel oil. This combustion process usually has a loud sound, leading to noise pollutants that can harm the environment and make passengers uncomfortable. Burning fossil fuels also causes the residual compounds that increases environmental pollution, especially carbon emissions. In this paper, an analysis will be carried out on the operational costs of a river cruise ship with electric paddle wheel propulsion. With a boat design with an LOA size of 5.4 m, breadth of 1.4 m, height of 0.8 m, draft of 0.3 m, and CB of 0.68, the paddle wheel diameter is 70 cm, blade width of 30cm, and 6 blades. The motor used to drive the paddle wheel has a power of 672.69 watts, with a battery capacity of 100 Ah. According to operational planning, benefits will be obtained, including zero carbon emissions, no noise and operational benefits can be up to 90% greater when compared to the out-board engine drive.